Effect of initial damage level and patch configuration on the fatigue behaviour of reinforced steel plates. Issue 3 (13th August 2014) - Colombi, P.; Fava, G.; Sonzogni, L.
ABSTRACT The application of carbon fibre reinforced polymer composites externally bonded on cracked steel plates is an effective system in extending the fatigue life of these structural elements. In particular, composite patches bonded on the crack tip region reduce the stress concentration and the crack opening displacement, leading to an extension of the fatigue life. In order to additionally show the effectiveness of this kind of reinforcing technique, experimental tests were performed at the laboratories of the Politecnico di Milano. Fatigue tests were executed on single edge notched tension specimens reinforced by pultruded strips bonded to a single side (non‐symmetric reinforcement). Different patch configurations (reinforcement stiffness and patch location) and initial damage levels were considered as parameters influencing the repair effectiveness in extending the fatigue life. The results showed that the use of carbon fibre reinforced polymer materials bonded around the tip region allows extending the fatigue life for different amount of initial damage level. Finally, this work provides some useful information for the more efficient repair configuration.